2002
DOI: 10.1055/s-2002-25023
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Recurrent Brief Depression with Reboxetine - A Single Case Analysis

Abstract: Recurrent Brief Depression (RBD) is a prevalent condition among the depressive illnesses, and is characterized by depressive episodes of a few days' duration occurring almost every month that are unrelated to the menstruation cycle. So far, RBD has not been shown to respond to antidepressive treatment in controlled clinical trials with citalopram, fluoxetine, flupenthixol, paroxetine, or mianserin using a "classical" parallel group design. However, successful RBD treatment on about sixty patients has so far be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
(10 reference statements)
1
6
1
Order By: Relevance
“…However, controlled studies were carried out with highly selected RBD patient samples for example, patients with repeated suicide attempts or comorbid borderline personality disorder or somatic diseases (Kocmur, Dernovsek & Tavcar, 1998;Montgomery et al, 1994;Verkes et al, 1998;Wermuth et al, 1998), and this might have led to a bias directed towards therapy resistance. Our own positive experience concerning treatment with mirtazapine (Stamenkovic, Pezawas, De Zwaan, Aschauer, & Kasper, 1998), reboxetine (Pezawas et al, 2002a), and fluoxetine, as well as other positive results from case reports with lithium (Corominas, Bonet & Nieto, 1998), carbamazepine (Gertz, 1992), lamotrigine (Malt & Fladvad, 2001) and tranylcypromine (Joffe, 1996) put the negative findings from other studies due to the above mentioned reasons in question (Pezawas et al, 2001).…”
Section: Treatmentmentioning
confidence: 72%
See 1 more Smart Citation
“…However, controlled studies were carried out with highly selected RBD patient samples for example, patients with repeated suicide attempts or comorbid borderline personality disorder or somatic diseases (Kocmur, Dernovsek & Tavcar, 1998;Montgomery et al, 1994;Verkes et al, 1998;Wermuth et al, 1998), and this might have led to a bias directed towards therapy resistance. Our own positive experience concerning treatment with mirtazapine (Stamenkovic, Pezawas, De Zwaan, Aschauer, & Kasper, 1998), reboxetine (Pezawas et al, 2002a), and fluoxetine, as well as other positive results from case reports with lithium (Corominas, Bonet & Nieto, 1998), carbamazepine (Gertz, 1992), lamotrigine (Malt & Fladvad, 2001) and tranylcypromine (Joffe, 1996) put the negative findings from other studies due to the above mentioned reasons in question (Pezawas et al, 2001).…”
Section: Treatmentmentioning
confidence: 72%
“…All in all those studies that chose a classical double-blind placebo-controlled two-tailed design were not able to demonstrate a successful treatment for RBD. Recent findings indicate that studies should be conducted using designs with an appropriate statistical sensitivity (e.g., single case analyses) and other statistical evaluation procedures as well as longer observation periods than used in MDD because of rapidly undulating symptoms specific for RBD (Pezawas, Stamenkovic, Aschauer, Moffat & Kasper, 2002a;Post et al, 1998a). Maybe this is how false negative study results came about and pessimism that was brought up in these controlled studies concerning possible successful therapy plans for RBD might be inappropriate.…”
Section: Treatmentmentioning
confidence: 99%
“…The clinical significance of this diagnostic concept has further been underlined by studies on patterns and consequences of a lifetime co-occurrence of both, RBD and MD, called combined depression (CD) (Montgomery et al 1989), which has been further developed by Angst (1990). Epidemiological (Angst, 1994 b;Maier et al 1994a) and clinical (Montgomery et al 1989 ;Pezawas et al 2002 a) studies demonstrated a dramatic increase of suicide attempt rates and measures of impairment in the case of CD in comparison to either single RBD or MD.…”
Section: Concept and Previous Findingsmentioning
confidence: 99%
“…The diagnosis of 'recurrent brief depressive disorder' was included within the group of 'depressive disorders not otherwise specified' in the Diagnostic and Statistical Manual of Mental Disorders, 4th ed.text revision (DSM-IV-TR) (American Psychiatric Association, 2000). Case reports and small case series suggest that patients with RBD may benefit from treatment with nimodipine (Pazzaglia et al, 1993), tranylcypromine (Joffe, 1996), mirtazapine (Stamenkovic et al, 1998), lithium (Corominas et al, 1998), fluoxetine (Stamenkovic et al, 2001), reboxetine (Pezawas et al, 2002), lamotrigine (Ravindran and Ravindran, 2007) and olanzapine (De la Fuente, 2008). This lack of progress in placing a diagnosis of RBD more firmly within the psychiatric nomenclature may in part stem from the absence of an established pharmacological or psychological treatment.…”
Section: Introductionmentioning
confidence: 99%